The southern Colesuyu: Space of Hispano-indigenous economic and cultural articulation in the second half of the 16th century - Choque Mariño, Carlos (2009)
This article analyzes the Hispanic-indigenous economic and cultural articulation during the second half of the 16th century in the southern area of ​​Colesuyu, located in the current region of Arica and Parinacota. The study tries to provide new background for the understanding of the cultural space of Colesuyu, as well as the economic and political relations that developed throughout this period and its importance for the construction of the ethnic identity of the indigenous population.